The Association of Biochemical Hypoglycemia with the Subsequent Risk of a Severe Hypoglycemic Event: Analysis of the DCCT Data Set - Roy W. Beck; Richard M. Bergenstal; Tonya D. Riddlesworth; Craig Kollman (2018)
To evaluate the association of biochemical hypoglycemia with subsequent severe hypoglycemia (SH) events using the Diabetes Control and Complications Trial (DCCT) data set.The frequency of biochemical hypoglycemia (percentage of values <70 and <54 mg/dL [3.9 and 3.0 mmol/L) was assessed using DCCT blood glucose concentrations measured at a central laboratory from seven finger-stick samples (7-point testing: pre- and 90-min postmeals and at bedtime) collected during 1 day every 3 months. SH events required a change in mental status necessitating the involvement of another individual to provide treatment. A Poisson model accounting for repeated measures from each participant was used to assess the association of biochemical hypoglycemia frequency, computed from the 7-point finger-stick data, with the development of SH events.The risk of SH during a 3-month period was substantially higher (P < 0.001) when there was at least one hypoglycemic blood glucose value in the preceding 7-point profile, with similar results seen for both the 70 mg/dL (rate ratio = 3.0 [95% confidence interval: 2.6-3.3]) and 54 mg/dL (rate ratio = 2.7 [95% confidence interval: 2.4-3.1]) thresholds.The occurrence of biochemical hypoglycemia <70 or <54 mg/dL is associated with an increased risk of SH. For this reason as well as the deleterious effects of hypoglycemia on glucose counter-regulation and hypoglycemia awareness, cognition, quality of life, and arrhythmias, it is important in diabetes management to avoid hypoglycemic glucose levels as much as possible.